Carboxylic ligands and their influence on the structural properties of PbTe quantum dots - Svetlana Lyssenko; Michal Amar; Alina Sermiagin; Refael Minnes (PLoS ONE, 2025)
We present a low-cost, straightforward, and tunable hot-injection method for synthesizing PbTe quantum dots (QDs). By incorporating short-chain carboxylic acids—hexanoic acid (HexA), heptanoic acid (HepA), and acetic acid (AcA)—alongside oleic acid (OA), we controlled QD morphology and size within the range of 13–17 nm. The resulting QDs exhibited a well-defined cuboctahedral shape and a core-shell structure, consisting of a crystalline core and an amorphous shell. Morphology and growth behavior were strongly influenced by precursor composition, ligand ratio, and steric hindrance. Compared to QDs synthesized with longer-chain acids (lauric (LA), decanoic (DA), and octanoic acids(OctA)), which produced multiple shapes, the use of shorter ligands led exclusively to uniform cuboctahedral nanocrystals. PbTe QDs are typically reported as cubic when their size exceeds 10 nm. In contrast, our method consistently produces cuboctahedral structures in this size range. QDs were characterized by high-resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). These findings open a route toward controlled shape engineering of PbTe QDs for future applications in quantum optics, infrared detectors, and thermoelectrics.